Analisis Motivasi Eksternal Dukungan Keluarga dan Lingkungan Kerja Non-Fisik terhadap Produktivitas Karyawan (Studi Terhadap Karyawan RSI Assyifa) - Ramadhan, Ihsan Fauzi; Nurmala, Resa; Saori, Sopyan (Universitas Muhammadiyah Pontianak, 2025)
This study evaluates the effect of external motivation, specifically family support and non-physical work environment, on employee productivity at RSI Assyifa. A quantitative method with a descriptive-associative approach was used involving 160 respondents. Regression analysis reveals both factors significantly and positively influence productivity. The non-physical work environment shows a more dominant contribution than family support. These findings suggest the importance of strengthening external aspects in the workplace to enhance productivity.